Effect of Electronic Cigarettes on Oral Microbial Flora - Gargin, V.V.; Nessonova, T.D.; Podrigalo, L.V.; Nakonechna, O.A.; Popova, T.M.; Kryvenko, L.S.; Tishchenko, O.V. (Journal of Pharmacy and Nutrition Sciences, 2021)
Background: Despite well-documented adverse effects of tobacco consumption, cigarettes use is still rising and part of this increase is related to the popularization of alternative electronic nicotine delivery devices, such as electronic cigarettes (ECs). The aim of the performed research was to assess the effect of electronic cigarettes aerosol on the oral microbiota, using culture methods. Methodology: 30 ten-week-old WAG rats (female 76-81 g and male 86-94 g) were randomly distributed in two groups, as follows: Group 1 – control animals (n = 10); Group 2 – EC aerosol exposed (n = 20). EC aerosol exposures were carried out by using the Boyarchuck chamber. During the study, the rat oral microbiota were collected four times: at the beginning of the experiment, on the 30th, 60th and 90th days. Microorganisms were identified using standard microbiological techniques. Results: EC exposure to Group 2 rats resulted in a depletion of colonies commensal microbes and a greater incidence of atypical species such as Klebsiella pneumoniae, Acinetobacter lwoffii, Candida albicans compared to Group 1 on day 90. The test of independence between frequency distibution of opportunistic microbes and duration of EC exposure showed a significance for Klebsiella pneumoniae – χ2= 8.017, p=0.0456, Acinetobacter lwoffii – χ2= 36.772, p=0.0001, and Candida albicans – χ2=8.689, p=0.0337. Conclusions: The impact of electronic cigarettes facilitated colonization of the oral cavity by opportunistic bacteria and yeast.